Antihyperglycemic/ Hypoglycemic Effect of Celery Seeds (Ajwain / Ajmod) in Streptozotocin induced Diabetic Rats - Khalid Niaz , Seemi Gull ,M. Azam Zia, (Journal of Rawalpindi Medical College, 2013)
Background:To investigate the effect of Apium graveolen L. (Celery seeds) on blood glucose and insulin concentrations in streptozotocin (STZ) induced diabetic rats. Methods: Forty Sprague Dawely rats weighing from 180 to 250 grams were randomly divided into four experimental groupsA,B,C &D, each containing ten (10) rats. Diabetes was induced by intraperitoneal administration of STZ (60mg/kg) in groups B,C&D,while group A served as normal control. The experimental animals became diabetic within 48 to 72 hours after administration of STZ.,Group B rats were taken as diabetic control. Alcoholic extract of Celery seeds, the test drug was administered (400mg/kg) orally to experimental gruop,C,while group D received standard drug glibenclamide.induced diabetic rats for six weeks. Normal control groupA& diabetic control B received only normal saline solution orally. Blood samples were collected from experimental groups after 43 days,24 hours of the last dose. ANOVA and Tukey HSD (Honestly Significant Difference) test applied to all groups. Results: The results show Celery seeds extract treatment caused a statistically significant decrease in the elevated serum glucose levels and increase in the serum insulin concentrations in test group C as compared to group B . Conclusion: Findings of present study provide evidence for traditional use of apium. graveolen in the control of diabetes.